Readiness to job stress in private and public enterprises. (6th May 2022) - Bhattacharya, Sonali; Neelam, Netra; Kunte, Monica
The purpose of this study was to find the impact of job stress on constructs of individual readiness to change, in the context of private and public sector employees. The impact of demographic variables has also been studied. Structural equation modelling was used to test the hypothesised model. Gender and age were used as control variables. Job stress was found to be inversely related to readiness to change. Further, the type of management of enterprises (public or private) moderates the relationship between job stress and constructs of individual readiness. At a given level of stress, public sector employees have significantly lower level of confidence, resourcefulness, passion, optimism, adaptability and tolerance and but higher level of adventurousness. Perceived stress and resourcefulness is higher among employees of the private sector. There are gender and age differences in some constructs of readiness to change. Females have higher job stress and stress increases with age.